Mood Dimensions Show Distinct Within-Subject Associations With Non-exercise Activity in Adolescents: An Ambulatory Assessment Study - Koch, Elena D.; Tost, Heike; Braun, Urs; Gan, Gabriela; Giurgiu, Marco; Reinhard, Iris; Zipf, Alexander; Meyer-Lindenberg, Andreas; Ebner-Priemer, Ulrich W.; Reichert, Markus (Frontiers in Psychology, 2018)
Physical activity is known to preserve both physical and mental health. However, the physical activity levels of a large proportion of adolescents are below the accepted recommendations. This is critical, since physical activity levels in youth have been shown to translate into adulthood, making the promotion of physical activity in adolescence a major health issue. In adult populations, mood has been suggested to be one important psychological factor that drives physical activity in everyday life, i.e., non-exercise activity. However, the association of mood and physical activity in adolescents’ everyday lives has been poorly studied. Ambulatory Assessment is the state-of-the-art approach to investigating how the association between mood and non-exercise activity waxes and wanes within persons in everyday life. Through assessments in real time and real life, this method provides ecological validity, bypassing several limitations of traditional assessment methods (e.g., recall biases). To investigate whether mood is associated with non-exercise activity in adolescents, we equipped a community-based sample comprising 113 participants, aged 12-17 years, with GPS-triggered e-diaries and accelerometers for use in their everyday lives for one week. We used multilevel analyses to compute the effects of several mood dimensions (i.e., valence, energetic arousal, and calmness) on non-exercise activity within 10-minute intervals following each e-diary prompt. Additionally, we conducted explorative analyses of the time course of the effects, i.e., on different timeframes of non-exercise activity up to 300 minutes following the mood assessment. The results showed that valence (p < 0.001) and energetic arousal (p < 0.001) were positively associated with non-exercise activity within the 10 minutes interval, whereas calmness (p < 0.001) was negatively associated with non-exercise activity. Specifically, adolescents who felt more content, full of energy, or less calm were more physically active in subsequent timeframes. Overall, our results demonstrate close associations of non-exercise activity with mood in younger ages and converge with the previously observed association between mood and physical activity in adults. In the future, we propose to investigate how these findings could be translated for use in interventions in adolescents’ everyday lives, e.g., using ambulatory assessment interventions.